2019
DOI: 10.1088/1742-6596/1318/1/012073
|View full text |Cite
|
Sign up to set email alerts
|

The ability of mathematical representation through realistic mathematics learning based on ethnomathematics

Abstract: Efforts to improve the mathematical representation, learning must begin from the real objects in daily life, which are culturally oriented related to horizontal mathematics in the form of ethnomathematics. The objective of this study was to determine the comparison of the ability of mathematical representation between students taught by realistic mathematical approach and conventional learning; determine the comparative ability of mathematical representation between students who are ethnomathematical and non-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The ability of students to understand mathematics given material oriented ethnomathematics was higher than students who studied non-ethnomathematics material after controlling students' initial abilities. This is for students to learn through realistic mathematical learning approaches [6,22,27]. Therefore, it is appropriate that learning mathematics through ethnomathematics be implemented in schools, and integrated with the curriculum.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of students to understand mathematics given material oriented ethnomathematics was higher than students who studied non-ethnomathematics material after controlling students' initial abilities. This is for students to learn through realistic mathematical learning approaches [6,22,27]. Therefore, it is appropriate that learning mathematics through ethnomathematics be implemented in schools, and integrated with the curriculum.…”
Section: Resultsmentioning
confidence: 99%
“…Ethnomathematics [11] is one of the approaches to this learning [12], by stating the point of realistic problems [13]. The results of the study showed that there were differences in the ability of mathematical representation between students who were taught by realistic mathematical approach and conventional learning; there is a difference in the ability of mathematical representation between students who are ethnomathematical and non-ethnomathematical oriented; there is an interaction effect of the learning approach and the orientation of mathematical material on the ability of mathematical representation [14].…”
Section: Resultsmentioning
confidence: 99%
“…The understanding of the number of students taught with associated learning in mathematics is better than that taught with traditional learning models. The overall score of the willingness of students to grasp the notion of numbers in students who received local culturebased material was greater than students who received local culture-based material (ethnomathematics) [27]. There are differences in mathematical abilities for students who are taught with realistic mathematics approaches compared with students taught with traditional learning.…”
Section: Figure 1: Example Of Tabutmentioning
confidence: 89%